Next-generation ammonia pretreatment enhances cellulosic biofuel production. Issue 4 (23rd February 2016) - da Costa Sousa, Leonardo; Jin, Mingjie; Chundawat, Shishir P. S.; Bokade, Vijay; Tang, Xiaoyu; Azarpira, Ali; Lu, Fachuang; Avci, Utku; Humpula, James; Uppugundla, Nirmal; Gunawan, Christa; Pattathil, Sivakumar; et al.
Abstract : Extractive ammonia pretreatment converts crystalline cellulose Iβ to a highly digestible cellulose IIII and selectively extracts up to ∼45% of the lignin from lignocellulosic biomass with near-quantitative retention of all polysaccharides. Abstract : A new liquid ammonia pretreatment methodology called Extractive Ammonia (EA) was developed to simultaneously convert native crystalline cellulose Iβ (CI) to a highly digestible cellulose IIII (CIII) allomorph and selectively extract up to ∼45% of the lignin from lignocellulosic biomass with near-quantitative retention of all polysaccharides. EA pretreated corn stover yielded a higher fermentable sugar yield compared to the older Ammonia Fiber Expansion (AFEX) process while using 60% lower enzyme loading. The EA process preserves extracted lignin functionalities, offering the potential to co-produce lignin-derived fuels and chemicals in the biorefinery. The single-stage EA fractionation process achieves high biofuel yields (18.2 kg ethanol per 100 kg untreated corn stover, dry weight basis), comparable to those achieved using ionic liquid pretreatments. The EA process achieves these ethanol yields at industrially-relevant conditions using low enzyme loading (7.5 mg protein per g glucan) and high solids loading (8% glucan, w/v).